METHODS OF DETERMINING THE LEVEL OF CONFIDENCE AND CALCULATING CONFIDENCE INDICATORS UNDER THE EVALUATION SYSTEM IN HIGHER EDUCATION (Marketing Journal, 2025)
This scientific article examines , from both theoretical and practical perspectives , the methodology for determining the level of trust in evaluation mechanisms within the higher education system and for calculating trust indicators . Within the scope of the study , the role of the concept of trust in the education system , approaches to measuring trust across different stakeholder groups , and a system of indicators formed through the integration of sociological and statistical methods are analyzed . It is substantiated that trust indices developed on the basis of an information -analytical approach contribute to enhancing the transparency and effectiveness of the evaluation system .
Keywords: higher education; evaluation system; level of trust; trust indicators; sociological survey; statistical analysis; integrated index; quality of education; stakeholders